Isolation of Lipase from Candlenut Seeds and Its Immobilization in Polyacrylamide Gel - Zella Yaumin Nasry; Nyoman Maya Krisnawati; Erin Ryantin Gunawan; Agus Abhi Purwoko; Lalu Rudyat Telly Savalas; Jannatin ‘Ardhuha (Jurnal Penelitian Pendidikan IPA, 2022)
In general, lipase enzymes are used in the form of free lipase enzymes which can only be used once and are less effective, so that their use is costly. Therefore, to maximize the use of the lipase enzyme, immobilization of the enzyme that allows multiple use is a choice. The purpose of this study was to determine the activity of the candlenut (Aleurites moluccana (L.) Wild) lipase in its free form and in immobilization form. The stability of the immobilized lipase enzyme with repeated use was also investigated. The enzyme was immobilized by trapping method using polyacrylamide gel. The immobilized lipase enzyme was characterized to determine its stability after repeated use with various gel concentrations. The crude extract of the lipase of candlenut seed sprouts had an activity of 2.32 U/mL, whereas the activity of the immobilized lipase enzyme in polyacrylamide gel at concentrations of 6%, 8%, and 10%, were 2.133; 2,259; and 2,311 U/mL, respectively. The optimum temperature for the immobilized lipase enzyme was 30 oC and the optimum pH was 7.5. After five time us usage, the immobilized enzyme showed activities of 49.49%, 72.60% and 86.53%, for 6%, 8% and 10% polyacrylamide gel, respectively. These results indicate that the immobilized lipase enzyme from seed sprouts of candlenut (Aleurites moluccana (L.) Wild) by trapping method using 10% polyacrylamide gel can maintain its stability after five times of use